Stabilisasi Lempung Lunak P. Rimau (Sum-Sel) Menggunakan Semen dan Bahan Kimia - Desiani, Asriwiyanti (Universitas Kristen Maranatha, 2003)
Development in Indonesia is partly on soft soils, for example the opening of transmigration areas and the construction of roads connecting cities on the east coast of Sumatra Island. The two main problems of construction on soft soils are large settlement and low bearing capacity. One of the soil improvement efforts that will be investigated is soil stabilization with cement and chemicals. Observations were only made on the bearing capacity of the soil using a free compressive strength tester. The stabilized soil type is soft clay with dominant mineral content of montmorillonite from P. Rimau, South Sumatra. The levels of cement mixed in the soil were 2, 6, 10 and 15% of dry weight with treatment periods of 1, 3, 7, 14 and 21. The chemicals used to improve cement properties in organic soils are NaOH, KOH and Na2CO3. The results showed an increase in strength both for the addition of cement content and for the addition of the treatment period. The increase in soil strength reached 500% - 1,450%.